Towards assessing online uncertainty for three-phase flow metering in the oil and gas industry - Henry, M; Tombs, MS; Zhou, F (Copernicus Publications, 2014)
A new three-phase (oil/water/gas) flow metering system has been developed for use in the oil and gas industries, based on Coriolis mass flow metering. To obtain certification for use in the Russian oil and gas industries, trials have taken place at the UK and Russian national flow laboratories, NEL in Glasgow and VNIIR in Kazan, respectively. The metrology of three-phase flow is complex, and the uncertainty of each measurement varies dynamically with the operating point, as well as the metering technology, and other aspects. To a limited extent this is reflected in the error limits allowed in national standards, which may vary with operating point. For example, the GOST standard allows errors in the oil flow rate of ±6% for water cuts of less than 70%, which is increased to ±15% for water cuts between 70 and 95%. The provision of online uncertainty for each measurement, for example in accordance with the British Standard BS-7986, would be highly desirable, allowing the user to observe in real time variations in measurement quality. This paper will discuss how an online uncertainty assessment could be implemented in the Coriolis meter-based system.